The effect of respiratory muscle training on aerobic and anaerobic strength in adolescent taekwondo athletes - Koç, M.; Saritas, N. (Journal of Education and Training Studies, 2019)
This study was conducted to investigate the effect of respiratory muscle training on respiratory functions and aerobic and anaerobic strength in adolescent taekwondo athletes. Between the ages of 12-17, 32 taekwondo athletes participated in the study. Participating athletes were randomly divided into two groups as ``experimental group`` (n=15) and ``control group`` (n=17) as to similar characteristics. The experimental group was given respiratory muscle training for 30 min with an adjustable respiratory pressure device for 3 days a week through 8 weeks period. No exercise was given to the control group with the device. A 20 meter shuttle run test was performed for aerobic capacity and a vertical jump test was performed for anaerobic strength. The inspiratory pressure was measured. After the respiratory muscle training, statistically significant difference was found in the maximum oxygen consumption capacities (MaxVO2) and anaerobic strength values (p<0.05). In the measurements of respiratory function, forced vital capacity (FVC), slow vital capacity (SVC) and maximal voluntary ventilation (MVV), significant difference was found in favor of the experimental group (p<0.05). In the measurements of inspiration pressure, the results of pressure, strength, flow, volume and energy values were significantly different in favor of the experimental group (p<0.05). Respiratory muscle training increased the aerobic and anaerobic strength capacity of the experimental group in comparison with the control group. Some of the exercises that were used in the treatment of COPD are thought to facilitate the athletes` respiration control.